2022
DOI: 10.1038/s41598-022-20408-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two injectable anaesthetic protocols in Egyptian fruit bats (Rousettus aegyptiacus) undergoing gonadectomy

Abstract: Egyptian fruit bats have gained increasing interest being a natural reservoir for emerging zoonotic viruses. Anaesthesia is often required to allow safe handling of bats. We aimed to compare the sedative and cardiopulmonary effects of two balanced anaesthetic protocols in bats undergoing gonadectomy. Group DK (n = 10) received intramuscular dexmedetomidine (40 µg/kg) and ketamine (7 mg/kg), whereas group DBM (n = 10) received intramuscular dexmedetomidine (40 µg/kg), butorphanol (0.3 mg/kg) and midazolam (0.3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 52 publications
0
6
2
Order By: Relevance
“…Several injectable anesthetics were described in bats for various procedures; however, specific controlled studies are relatively sparse. In bats, medetomidine- or dexmedetomidine-based protocols were reported to provide deep sedation or anesthesia ( 1 , 8 , 10 , 11 ). Alpha-2-adrenergic agonists tend to produce significant effects on the cardiovascular system (initial hypertension, profound reflex bradycardia and poor peripheral circulation) ( 11 , 33 , 34 ), therefore, they were avoided in the present report.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several injectable anesthetics were described in bats for various procedures; however, specific controlled studies are relatively sparse. In bats, medetomidine- or dexmedetomidine-based protocols were reported to provide deep sedation or anesthesia ( 1 , 8 , 10 , 11 ). Alpha-2-adrenergic agonists tend to produce significant effects on the cardiovascular system (initial hypertension, profound reflex bradycardia and poor peripheral circulation) ( 11 , 33 , 34 ), therefore, they were avoided in the present report.…”
Section: Discussionmentioning
confidence: 99%
“…Although not reported in bats, the authors applied local anesthetic techniques previously reported in other species during gonadectomies ( 31 , 32 ), to provide better analgesia and to increase animal welfare. Although locoregional techniques were not used by Amari et al it was recommended by the authors for bat gonadectomies ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations